ESTIMATION OF ZINC CONTENT IN HUMAN LUNG AND LIVER AUTOPSY TISSUE SAMPLES: A STUDY ON THE POPULATION OF AJMER (INDIA) (Applied Biological Research, 2023)
Zinc (Zn) is an important element in human biological system. Human autopsy wet tissues (67) of lungs and liver, collected at random from  Ajmer population of Rajasthan (India), were analyzed for Zn content.  The samples were taken from non-putrefied dead bodies received at JLN Medical College (JLNMC), Ajmer. The samples from human undergone  death due to burn injury or drowning were not considered. Seven  demographic data for each case were collected from their medical status  reports (post-mortem report) and from the pathological and anatomical  reports available at the Forensic Medicine Department, JLNMC and also  from the relatives of sampled human cases. Fresh autopsy tissues were  digested in di-acid and analyzed by graphite furnace atomic absorption  spectrometry. In lungs and liver, the average Zn content was 26.4 and  46.1 µg g-1, respectively. The Zn content in lungs and liver samples  varied from 11.59 to 97.51 and 26.63 to 114.29 µg g-1, respectively. In  females the mean Zn levels were higher than males in both lung and  liver. Rural residents had higher mean Zn content than peri-urban  and urban residents. In occupation environment sub-group exposed to  polluted area had low mean Zn content than non-exposed cases.
Keywords: Autopsy; demographic profile; human; liver; lung; zinc